Iron bioavailability of maize (Zea mays L.) after removing the germ fraction - Keigler, Johanna I.; Wiesinger, Jason A.; Flint-Garcia, Sherry A.; Glahn, Raymond P. (Frontiers in Plant Science, 2023)
Maize is a staple food for many communities with high levels of iron deficiency anemia. Enhancing the iron concentrations and iron bioavailability of maize with traditional breeding practices, especially after cooking and processing, could help alleviate iron deficiency in many of these regions. Previous studies on a small number of maize genotypes and maize flour products indicated that degermination (germ fraction removed with processing) could improve the iron bioavailability of maize. This study expanded upon this research by evaluating the iron bioavailability, mineral concentrations, and phytate concentrations of 52 diverse maize genotypes before (whole kernels) and after degermination. Whole and degerminated maize samples were cooked, dried, and milled to produce corn flour. Iron bioavailability was evaluated with an in vitro digestion Caco2 cell bioassay. In 30 of the maize genotypes, bioavailable iron increased when degerminated, thus indicating a higher fractional iron uptake because the iron concentrations decreased by more than 70% after the germ fraction was removed. The remaining 22 genotypes showed no change or a decrease in iron bioavailability after degermination. These results confirm previous research showing that the germ fraction is a strong inhibitory component for many maize varieties. Phytate concentrations in maize flours were greatly reduced with degermination. However, the relationship between phytate concentrations and the iron bioavailability of processed maize flour is complex, acting as either inhibitor or promoter of iron uptake depending on the color of the maize kernels and processing method used to produce flour. Other factors in the maize endosperm fractions are likely involved in the effects of degermination on iron bioavailability, such as vitreous or floury endosperm compositions and the polyphenol content of the bran. This study demonstrates that iron nutrition from maize can be enhanced by selecting genotypes where the inhibitory effect of the bran color and endosperm fraction are relatively low, especially after processing via degermination.